2015
DOI: 10.21273/hortsci.50.10.1562
|View full text |Cite
|
Sign up to set email alerts
|

Relative Salt Tolerance of Seven Texas Superstar® Perennials

Abstract: Salt tolerance of seven Texas Superstar® perennials [Malvaviscus arboreus var. drummondii (Turk’s cap), Phlox paniculata ‘John Fanick’ (‘John Fanick’ phlox), Phlox paniculata ‘Texas Pink’ (‘Texas Pink’ phlox), Ruellia brittoniana ‘Katie Blue’ (‘Katie Blue’ ruellia), Salvia farinacea ‘Henry Duelberg’ (‘Henry Duelberg’ salvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
52
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 14 publications
8
52
2
Order By: Relevance
“…2D). Similarly, Sun et al (2015) reported that the number of shoots of M. arboreus, S. leucantha, and V. ·hybrida decreased significantly when irrigated with saline solution at an EC of 10.0 dS · m -1 for 8 weeks, whereas the number of shoots of S. farinacea was not reduced. Although the number of shoots of T. scaposa tended to decrease with saline solution irrigation at an EC of 10.0 dS · m -1 for 5 weeks but still was not significant (Wu et al, 2016b).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…2D). Similarly, Sun et al (2015) reported that the number of shoots of M. arboreus, S. leucantha, and V. ·hybrida decreased significantly when irrigated with saline solution at an EC of 10.0 dS · m -1 for 8 weeks, whereas the number of shoots of S. farinacea was not reduced. Although the number of shoots of T. scaposa tended to decrease with saline solution irrigation at an EC of 10.0 dS · m -1 for 5 weeks but still was not significant (Wu et al, 2016b).…”
Section: Resultsmentioning
confidence: 80%
“…Saline solution at an EC of 10.0 dS · m -1 decreased the SPAD readings of A. barnebyi and E. septentrionale by 17.7% and 6.2%, respectively. Similarly, Sun et al (2015) documented that the SPAD readings of M. arboreus, R. brittoniana, and V. ·hybrida did not change, but S. farinacea and S. leucantha decreased significantly when irrigated weekly with saline solution at an EC of 10.0 dS · m -1 for 8 weeks. In a study of rose rootstocks by Niu et al (2008), Rosa ·fortuniana had greater SPAD readings compared with R. ·multiflora and R. ·odorata when irrigated with saline solution at an EC of 6.0 dS · m -1 for 15 weeks.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Salinity tolerance varies among plant species, and selecting salt-tolerant plants and using them in landscapes can be sustainable. Salinity-tolerant plants are usually identified by manually irrigating plants with saline solutions (Liu et al, 2017;Sun et al, 2015). However, this protocol is time-consuming and only applicable to a limited number of plants.…”
mentioning
confidence: 99%